Tea prices continue moving skyward - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Strong consumer demand and unusual climatic conditions in some of the major tea producing countries have pushed tea prices at auction centres around the world to the highest levels in decades. Between January and December 1997 the world's main...